An Online Multidomain Validation Method for Wireless Sensor Nodes - Changjian Deng; Dongyi Chen; Heng Zhang; Hongyang Hu; Jianzhong Lin (International Journal of Distributed Sensor Networks)
If wireless sensor network was deployed in electric power plants to provide equipment health data, it is essential that the data should be accurate and reliable. Nodes of wireless sensor network are different than wired test units, for they need to be distributed and have some constrains. Then online validation method is important to ensure data of networks to be reliable in important and safety related fields. It has been proved that calculation (such as FFT) can be validated by two orders functional (e.g., energy) in time and frequency domain, and with doing different number of times time-frequency signal analysis, the principle of test signal measurement validation method has been introduced. And with steady state signal, metastable signal, and the nonstationary signal the different online validation method is presented. And this method has been proved to be highly reliable and less uncertain in theory and experiment.